2002
DOI: 10.1034/j.1600-0897.2002.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia: A Multifactorial Disease Resulting from the Interaction of the Feto‐maternal HLA Genotype and HCMV Infection

Abstract: The results suggest that the presence of alleles HLA-G*0104, DRB1*07/06, HCMV sequences and the fetal inheritance of maternal G*0104, should be considered as conditioning factors for the development of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 40 publications
1
41
1
Order By: Relevance
“…On the other hand, Hviid et al [58] genotyped 61 RSA couples and 47 fertile control couples and did not observe any significant differences in the distribution of the above HLA-G alleles. The analysis of variations in the HLA-G gene exons also was addressed regarding PE: A study by Carreiras et al [74] observed a preferential inheritance of maternal G*0104 alleles among 25 PE mother-child pairs. This result was not observed in a Danish study including 57 family triads (offspring and parents) with PE and 98 control families, in which no obvious differences were observed in the distribution of the HLA-G alleles [62].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Hviid et al [58] genotyped 61 RSA couples and 47 fertile control couples and did not observe any significant differences in the distribution of the above HLA-G alleles. The analysis of variations in the HLA-G gene exons also was addressed regarding PE: A study by Carreiras et al [74] observed a preferential inheritance of maternal G*0104 alleles among 25 PE mother-child pairs. This result was not observed in a Danish study including 57 family triads (offspring and parents) with PE and 98 control families, in which no obvious differences were observed in the distribution of the HLA-G alleles [62].…”
Section: Discussionmentioning
confidence: 99%
“…Various small studies have linked disorders of pregnancy such as recurrent miscarriage [21,22] and preeclampsia [23,24] with HLA-G, but the alleles implicated vary, and several studies found no associations [25][26][27]. Because much of the limited polymorphism is in untranslated regions or encodes synonymous changes, associations are also of uncertain significance until biological mechanisms are described that might underlie the genetic findings.…”
Section: Disease Association Studiesmentioning
confidence: 92%
“…HCMV is associated with several vascular diseases, including atherosclerosis, coronary heart disease, and vasculopathy [5][6][7]. During pregnancy, HCMV infections have also been associated with the hypertensive disorder preeclampsia [7][8][9].…”
Section: Introductionmentioning
confidence: 99%